Assessing work ability - a cross-sectional study of interrater agreement between disability claimants, treating physicians, and medical experts - Salome Dell-Kuster; Simon Lauper; Joerg Koehler; Johanna Zwimpfer; Benedikt Altermatt; Tibor Zwimpfer; Leon Zwimpfer; Jim Young; Heiner C Bucher; Alain J Nordmann (Nordic Association of Occupational Safety and Health (NOROSH), 2014)
OBJECTIVES: It is unclear to what extent assessments of work ability differ between disability claimants, their treating physicians, and multidisciplinary medical expert teams. METHODS: We compared assessments of work ability for consecutive disability claimants referred to a multidisciplinary assessment center in Switzerland over a 4-year period. Assessments were made for the last job (LJ) prior to claiming a disability benefit and an alternative job (AJ) thought to suit the claimant's physical and mental abilities. Mean differences (MD) in percentage work ability between assessments from claimants, physicians, and experts were then estimated in a linear regression model. RESULTS: The 3562 claims made during the study period were mostly due to musculoskeletal and depressive disorders. Assessments differed little between claimants and physicians [LJ MD 1.3% (95% confidence interval [95% CI] 0.5-2.2%); AJ MD 11% (95% CI 10-12%)]. Experts on average assessed a claimant's work ability higher than either the claimant or physician, particularly in the AJ [MD between expert and claimant 57% (95% CI 56-58%) and between expert and physician 46% (95% CI 45-48%)]. CONCLUSIONS: Assessments of work ability differed substantially between experts in multidisciplinary medical teams and both claimants and their treating physicians. A careful evaluation of the disability assessment process is needed in an effort to reduce disagreement between expert teams and treating physicians and so improve acceptance of the process.